The Complex Architecture of Plant Cuticles and Its Relation to Multiple Biological Functions - Reynoud, Nicolas; Petit, Johann; Bres, Cécile; Lahaye, Marc; Rothan, Christophe; Marion, Didier; Bakan, Bénédicte (Frontiers in Plant Science, 2021)
Terrestrialization of vascular plants i.e. Angiosperm, is associated with the development of cuticular barriers that prevent biotic and abiotic stresses and support plant growth and development. To fulfill these multiple functions, cuticles have developed a unique supramolecular and dynamic assembly of molecules and macromolecules. Plant cuticles are not only an assembly of lipid compounds, i.e. waxes and cutin polyester, as generally presented in the literature, but also of polysaccharides and phenolic compounds, each fulfilling a role dependent on the presence of the others. This mini-review is focused on recent developments and hypotheses on cuticle architecture-function relationships through the prism of non-lipid components, i.e., cuticle-embedded polysaccharides and polyester-bound phenolics.